A content analysis of motion illustration as a tool for enhancing audience engagement in radio broadcasts/ Miesya Dania Mohd Zahiruddin ... [et al.] - Mohd Zahiruddin, Miesya Dania; Mohd Lazim, Nur Aniza; Omar, Mastura; Mohd Muslim Tan, Ellyana; Ishak, Siti Norfatulhana (Universiti Teknologi MARA, Perak, 2024)
This study aims to explore the effectiveness of motion illustration as a tool for enhancing audience engagement in radio broadcasts. The use of motion illustration in radio broadcasts is a relatively new phenomenon that has the potential to improve audience engagement and increase listener retention. The study examines the impact of motion illustration on audience engagement by conducting a survey of listeners of a radio station that has implemented motion illustration in their broadcasts. The survey data is analysed using statistical methods, and the findings suggest that motion illustration is an effective tool for enhancing audience engagement in radio broadcasts. The study concludes by recommending a diverse range of motion illustration for radio stations seeking to integrate motion illustration into their broadcasts, aiming to enhance audience engagement and boost listener retention.